ANALISIS PERSEPSI MASYARAKAT DESA KUALA PANDUK TERHADAP LARANGAN PERKAWINAN EKSOGAMI PEREMPUAN SUKU AJO DESA KUALA PANDUK KECAMATAN TELUK MERANTI (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the belief of the Ajo tribe, Kuala Pandukvillage, Teluk Meranti sub-district with the prohibition of exogamous marriage for Ajoethnic women. Where the Ajo tribe woman who wants to get married must be withmembers of her tribe. This rule only applies to women of the Ajo tribe. However, theresearchers found that there were violations committed by the Ajo woman. Theformulation of the problem in this research is How the Perception of the Kuala PandukVillage Community Against the Prohibition of Exogamous Marriage of Ajo TribeWomen in Kuala Panduk Village, Teluk Meranti District. The purpose of this study wasto determine the perceptions of the people of Kuala Panduk village against theprohibition of exogamous marriage of Ajo Tribe women in Kuala Panduk village, TelukMeranti district. This research method is qualitative, there are 10 informants in thisstudy who fulfill the characteristics of informants using the Snowball Samplingtechnique. Data collection techniques using interviews, observation, anddocumentation. For data analysis techniques in this study by means of data reduction(data reduction), data display (data presentation) and Conclusion / Verification(conclusion). The perception of the people of Kuala Panduk village against theprohibition of exogamous marriages for Ajo ethnic women is that they do not agree withthe prohibition of exogamous marriages because they do not violate syara laws'.Religion also does not prohibit as in QS. Al-Hujurat: 13. Disagreeing with thisprohibition according to the people of Kuala Panduk village regarding the law thatexogamous marriage may be implemented because it does not violate religiousteachings, and now there are no strict sanctions like in the past against offenders sothat many have committed violations. When they commit an offense there is no impact,such as a bad life or the like which they divorced in the past.Key Words: Perception, Exogamous, Ajo Tribe